Single Stem Silviculture - Sagreiya, K. P. (Indian Forester, 1955)
Suggests the use of the 'normal' N/D correlation for teak of coppice-origin in the same manner as the N/V correlation has been used by O'Connor for solving a variety of specific problems connected with thinning regimes, in his paper on Forest Research with special reference to Planting Distances Submitted to the British Empire Forestry Conference, South Africa, 1935. A simpler notation has been used. Part I deals with definitions and the theory involved. The Basic Graph A gives the normal N/D Curve, the Free Growth Zone, the Suppression Zone and the Normal N/D year-lines. Suppression and Response are mathematically expressed and it is shown how the crop-diameter at any age under specified suppression or response could be arrived at. The Basic Graph B gives the correlation between Suppression and Response. Part II deals with the application of the two Basic Graphs to specific problems, viz., ( I ) the shortest rotation at which the largest number of elites could attain a desired size; ( ii ) the largest number of elites that could be grown per acre to obtain the maximum volume without thinnings; ( iii) the optimum thinning regime to obtain the highest total yield of the largest size of poles; ( iv ) the effect of competition between elites on the total yield; ( v ) the effect of one delayed thinning on the total yield. How allowance for increase in crop-diameter after a thinning and the true relationship between the coefficients of Suppression and Response could be made is also shown. Part III describes how plots could be laid out and measured to obtain the basic N/D year-lines normal N/D Curve, and a graphical correlation between Suppression and Response. It is urged that the theory outlined be tested by research workers.